Indomie sebagai Simbol Kosmolokalisme: Studi Kualitatif tentang Integrasi Budaya Global-Lokal di Nigeria - Ardhan, Aulia Jabbar (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
In today’s globalized world, food serves not only as a basic necessity but also as a medium for uniting cultures and reinforcing local identity. This qualitative study explores how Indomie, a popular Indonesian instant noodle brand, fosters cosmolocalism in Nigeria by functioning as both a consumer product and a cultural integrator. Through a thematic analysis of secondary sources—including scholarly literature, reports, and media—this research examines how Indomie is localized within Nigerian culinary practices without diminishing cultural uniqueness. The findings reveal that Indomie operates as a symbol of intercultural exchange, reflecting how global products can be adopted and transformed within local contexts. Moreover, the study highlights the role of gastro-diplomacy and cross-national economic cooperation in strengthening bilateral cultural ties. These insights offer new perspectives on the intersection of food, identity, and global-local dynamics.